Hofoper in Schwetzingen: Musik, Bühnenkunst, Architektur - Leopold, Silke; Pelker, Bärbel; Frese, Annette; Hirschmann, Juliane (Winter, 2004)
Inhalt: Musik- und Operngeschichte (1753-1785) -- Baugeschichte (1752-2004)